Clinical and Etiological Profile of Patients with Atrial Fibrillation (AF): Analysis and implications (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: Atrial fibrillation (AF) is a frequently encountered cardiac arrhythmia which may be either symptomatic or asymptomatic. So, this study was conducted to know clinical presentation and to find out possible clinical and etiological profile of patients with AF.Material and Methods: This cross sectional study was conducted at Osh Regional Integrated Clinical Hospital, Osh Territorial City Clinical Hospital, The Kyrgyz Republic in collaboration with Janaki Medical College Teaching Hospital, Janakpurdham, Nepal. Sixty consecutive patients with AF were taken. Presenting complaints, past history, personal history was recorded. A thorough clinical examination was done, electrocardiogram, chest X-Ray posterio-anterior view, echocardiogram, thyroid function test and relevant test were done and analyzed.Results: Forty percent of the patients complained palpitation. Systemic thrombo-embolism was found in 15% of the patients. Other presenting complaints were cough, chest pain, shortness of breath, dizziness, swelling of the legs, tremors. Eighteen percent of patients presented with features of congestive cardiac failure and 30% of the patients gave history of rheumatic heart disease, 16.6% and 11.6% hypertension and ischemic heart disease respectively. Etiology-wise, rheumatic heart disease was the most common (46.6%) followed by hypertension (21.6%), ischemic heart disease (11.6%), dilated cardiomyopathy (6.6%), hyperthyroidism (5%), pneumonia (5%).Conclusion: Rheumatic heart disease, especially mitral stenosis is the most common cause of AF in this study. Systemic hypertension was next common etiology of AF, followed by ischaemic heart disease, dilated cardiomyopathy, thyroid disease. Heart failure, Systemic thromboembolism, decreased exercise tolerance are a major determinants for development of significant morbidity and mortality.Janaki Medical College Journal of Medical Sciences (2016) Vol. 4 (1): 5-12